Memutuskan Belenggu Okultisme: Sebuah Kajian Alkitabiah - Elieser Maratimbul Hutabarat; Rencan Charisma Marbun (Jurnal Masyarakat Indonesia (Jumas), 2024)
This research investigates the Biblical perspective on occultism and provides practical guidelines for liberation from occult practices. Occultism is regarded as an act that violates God's law and potentially brings negative effects spiritually, emotionally, and physically to those involved. Based on the analysis of Biblical texts, it is found that the Bible clearly prohibits practices such as sorcery, divination, and contact with evil spirits. Recommended liberation steps include confession of sins, genuine repentance, destruction of occult-related objects, and strengthening faith through God's Word and community support. Support from the church and spiritual counselors is also crucial in ensuring sustainable liberation and comprehensive spiritual recovery.